Reclassification of Cybistrinae Sharp, 1880 in the Neotropical Region (Coleoptera, Adephaga, Dytiscidae), with description of new taxa - Miller, Kelly B. (2024)
The classification of the Neotropical Cybistrinae Sharp, 1880 (Coleoptera: Adephaga: Dytiscidae) is extensively revised based on a phylogenetic analysis of morphological features of the group. A new genus, Nilssondytes gen. nov. is described for a unique new species, Nilssondytes diversus sp. nov. from Venezuela. The New World genus, Megadytes Sharp, 1882, with several subgenera, was found to not be monophyletic. The type species of Megadytes, Dytiscus latus Fabricius, 1801 and the species Cybister parvus Trémouilles, 1984 were found to be monophyletic together, and phylogenetically more closely related to Cybister Curtis, 1827 than to other species assigned to Megadytes sensu stricto, which were found to also be monophyletic. The name Megadytes is here restricted to include only Megadytes latus and Megadytes parvus. These two species assigned to this newly restricted genus concept are reviewed and diagnosed. A new genus, Metaxydytes gen. nov., is erected to include all the other species currently assigned to Megadytes sensu stricto. The current subgenus names assigned to Megadytes, Bifurcitus Brinck, 1945, Paramegadytes Trémouilles & Bachmann, 1980, and Trifurcitus Brinck, 1945, are elevated to genus rank since they are variously paraphyletic. The two species assigned to Cybister (Neocybister) Miller, Bergsten & Whiting, 2007, Cybister (Neocybister) festae Griffini, 1895, and Cybister (Neocybister) puncticollis (Brullé, 1837) re reviewed and diagnosed with the former redescribed and its type specimens considered for the first time since its description. Another evidently new species and possible new genus, Megadytes species, IR57 (Ribera et al. 2008), from Peru, is also characterized, but not formally treated because of lack of important data for the single, partial specimen. Diagnostic features are illustrated for the entire group.